2020
DOI: 10.38036/jgpp.11.4_22
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Computational Aeroelasticity Of Civil Fan Blades

Abstract: This paper presents a review of aeroelasticity research concerning fan blades in modern civil aircraft engines. It summarises the research carried out at the Rolls-Royce Vibration University Technology Centre (VUTC) at Imperial College over the past 25 years. The purpose of this paper is to gather information on all the aeroelastic issues observed for civil aero-engine fan blades into one document and provide a useful synopsis for other researchers in the field. The results presented here are based on numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Closer to the fanface (đť‘Ą * = 0.9), the amplitude of static pressure Ĺ•uctuations associated with blade-passing was dominant although a low-frequency signature due to the aero-mechanical response of the compression system, particularly relative to high-cycle fatigue and resonance analysis [55]. This is particularly true for high-loaded fan blades such as those of a low-speed fan [56,57]. Thus, for a closely coupled fan-intake in crosswind conditions, the inĹ•uence of intake design on the temporo-spatial characteristics of the intake Ĺ•ow distortions has to be determined.…”
Section: Space-time Characteristics Of Flow Distortionsmentioning
confidence: 97%
“…Closer to the fanface (đť‘Ą * = 0.9), the amplitude of static pressure Ĺ•uctuations associated with blade-passing was dominant although a low-frequency signature due to the aero-mechanical response of the compression system, particularly relative to high-cycle fatigue and resonance analysis [55]. This is particularly true for high-loaded fan blades such as those of a low-speed fan [56,57]. Thus, for a closely coupled fan-intake in crosswind conditions, the inĹ•uence of intake design on the temporo-spatial characteristics of the intake Ĺ•ow distortions has to be determined.…”
Section: Space-time Characteristics Of Flow Distortionsmentioning
confidence: 97%
“…This effect can be either stabilising or destabilising, depending on the phase difference between vibration and reflected wave. Several studies describe these effects and present analytic [7] and numerical methods [8], [9] to address the coupled aerodynamic damping. Since CA3ViAR is aiming at generating flutter conditions, the coupling of intake and rotor must be resolved and quantified during the design process.…”
Section: Flutter Analysis and Stability Mapmentioning
confidence: 99%
“…The fan is made of titanium and manufactured as a blisk. Thus, the mechanical damping is negligible, and aerodynamic damping is crucial in determining the aeroelastic stability [9].…”
Section: Aecc Cae Wide Chord Fan Rigmentioning
confidence: 99%
“…Some factors have been identified to have an important influence on blade flutter, e.g., mode coupling [1,2], inter blade phase angle (IBPA) [3], tip clearance flow [4], mistuning [5], interaction between stages [6,7], and acoustic reflections [8]. In particular, Vahdati et al [9] concluded that wide chord fan blade flutter usually occurs in the 1F mode when the inlet relative Mach number at the fan tip is close to the unit. They classified civil wide chord fan blade flutter into two types: classical stall flutter and acoustic flutter.…”
Section: Introductionmentioning
confidence: 99%